Sound Recording, Processing and Installation for Pedagogical Purposes - Dimitrov, Milen (Педагогически форум, 2021)
One of the current problems facing modern academic training of students in pedagogical programs is the formation of digital competencies in the field of music. The skills for sound recording, processing and editing with the means of technology are extremely useful effects with various projections in pedagogical theory and practice. The article describes a study of students' attitudes towards the implementation of a team task related to the development of an audio product for pedagogical purposes